(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Digital transformation is a process that is increasing the impact of technology on society and the economy, which is currently causing significant changes all over the world. This process is widely used in various fields, in particular, business, healthcare, education, manufacturing and everyday life. The article analyzes the role and impact of digital technologies, such as IoT (Internet of Things), 5G, artificial intelligence and blockchain, on society and the economy. Technologies are automating various aspects of our lives, increasing efficiency, creating new jobs and leading to the development of business models. However, we also consider the risks of digital transformation, in particular, information security, privacy and technological disruptions. The article sheds light on the future of digital transformation and its opportunities.